Developing Positive Behavior Based on Pancasila Character Values in Primary School Settings - Nur Ali Yasin YASIN (Master of Civic Innovation and Education Technology, 2026)
This study examines the development of positive student behavior through the internalization of Pancasila character values in a rural elementary school. The study was conducted at SDN 2 Kalipuro using a qualitative descriptive approach through observation, interviews, and documentation. The results indicate that the five principles of Pancasila (belief in God, humanity, unity, democracy, and social justice) are implemented in various routine school activities, such as religious activities, peer solidarity programs, flag ceremonies, school deliberations, and mutual cooperation activities. These practices reflect a school-based social learning process, where modeling behavior, habituation, and interaction form the basis for the formation of students' moral and prosocial character. Despite several obstacles, such as uneven student participation and a lack of self-confidence, this study demonstrates that a values-oriented school culture and consistent role modeling can effectively shape positive behavior. These findings contribute to the development of school psychology and character education, particularly in the context of schools with limited resources.